Negotiations and change : from the workplace to society - Kochan, Thomas A.; Lipsky, David B., 1939- (ILR Press, an imprint of Cornell University Press, 2003)
Major changes within and between organizations are now generally negotiated by the parties that have a stake in the consequences of the changes. This was not always so. In 1965, with A Behavioral Theory of Labor Negotiations, Richard Walton and Robert McKersie laid the analytical foundation for much of the innovation in the practice of negotiation that has occurred over the last thirty-nine years. Since that time, however, the field has undergone significant changes, and Walton and McKersie's ideas have been applied to a wide variety of situations beyond labor negotiations. Negotiations and Change represents the next generation of thinking. Experts on negotiations, management, and organizational behavior take stock of what has been learned since 1965. They extend and apply the concepts of Walton and McKersie and of other leaders in the study of negotiations to a broad range of business, professional, and personal concerns: workplace teams, conflict management systems, corporate governance, and environmental disputes. While building on those foundations, the essays demonstrate the continued robustness and relevance of Walton and McKersie's behavioral theory by suggesting ways it could be used to improve the management of change. Returning to its roots, the volume concludes with a retrospective by Richard Walton and Robert McKersie.